2019
DOI: 10.1002/asia.201901380
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalyzed Synthesis of Functionalized Quinolines

Abstract: As one of the most widely investigated compound skeleton, quinolines possess important medicinal and biological activities. As such, ag reat number of literatures, including reviews, have reported various methodologies to construct quinolines. Recently,o rganocatalyzed reactions have attracted the attention of organic chemists due to its being "green" because the reactions avoid the use of toxic metals.I nt his review, various distinctive contributionsa re surveyed with specific emphasis on organocatalyzed rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…[15,16] The conundrum is that homogeneous reactions usually entail tedious separation of catalyst residues, whereas the use of heterogeneous catalysts leads to undesired side reactions. [17,18] There is therefore a compelling need to develop SACs that enable efficient access to valuable quinoline derivatives with high selectivity and are easily separable from the reaction mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…[15,16] The conundrum is that homogeneous reactions usually entail tedious separation of catalyst residues, whereas the use of heterogeneous catalysts leads to undesired side reactions. [17,18] There is therefore a compelling need to develop SACs that enable efficient access to valuable quinoline derivatives with high selectivity and are easily separable from the reaction mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…This involves utilizing various catalysts such as transition metals, photocatalysts, and organo‐catalysts, which have demonstrated their efficacy in initiating desired reactions. Aniline, 2‐substituted aniline, and N ‐substituted aniline derivatives are commonly utilized as substrates [91,94–98] . In these substrates, aniline serves as a nitrogen‐carbon‐carbon (N−C−C) building block, 2‐substituted aniline functions as a nitrogen‐carbon‐carbon‐carbon (N−C−C−C) precursor, and N ‐substituted aniline acts as a carbon‐nitrogen‐carbon‐carbon (C−N−C−C) synthetic agent.…”
Section: Quinolinesmentioning
confidence: 99%
“…Aniline, 2-substituted aniline, and N-substituted aniline derivatives are commonly utilized as substrates. [91,[94][95][96][97][98] In these substrates, aniline serves as a nitrogen-carbon-carbon (NÀ CÀ C) building block, 2-substituted aniline functions as a nitrogen-carbon-carbon-carbon (NÀ CÀ CÀ C) precursor, and N-substituted aniline acts as a carbon-nitrogen-carbon-carbon (CÀ NÀ CÀ C) synthetic agent.…”
Section: Synthetic Strategies Of Quinolinementioning
confidence: 99%
“…16 a , b A comprehensive literature survey indicates that very few methods are available for obtaining molecules with quinone cores fused to quinoline or dihydroquinoline. These methods used syncarpic acid and rapanone as starting materials, which pose a significant challenge for synthesizing C-alkylation derivatives 17 (Scheme 1). In 2015, Nishimura et al reported the C-alkylation of syncarpic acids by Friedel–Crafts acylation of phloroglucinol, followed by tetra-methylation and reduction.…”
Section: Introductionmentioning
confidence: 99%